2024
DOI: 10.1111/apt.17950
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle mass increases after viral eradication with direct‐acting antivirals in patients with chronic hepatitis C: A longitudinal study

Marta Paula Pereira Coelho,
Thais Pontello de Vries,
Aline Marcos Pires
et al.

Abstract: SummaryBackgroundResults of studies evaluating the effect of viral eradication following direct‐acting antiviral (DDA) therapy on skeletal muscle mass of patients with chronic hepatitis C (CHC) are scarce.AimTo assess the components of sarcopenia (low muscle mass, low muscle strength and low physical performance) in a cohort of CHC individuals before and after DAA therapy.MethodsWe performed a longitudinal study of patients with CHC who underwent body composition assessment before (T0), and at 12 (T1) and 48 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…4 In our study, hepatitis C virus (HCV) eradication following direct-acting antiviral therapy was associated with an increase of 0.20 and 0.22 kg/m 2 in SMI at Weeks 12 and 48 following the end of antiviral treatment, respectively. 2 Although the muscle-liver crosstalk in chronic hepatitis C (CHC) is not wholly clarified, we observed a dynamic reduction in non-invasive markers of hepatic fibrosis and increased muscle mass in patients who have achieved HCV eradication.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…4 In our study, hepatitis C virus (HCV) eradication following direct-acting antiviral therapy was associated with an increase of 0.20 and 0.22 kg/m 2 in SMI at Weeks 12 and 48 following the end of antiviral treatment, respectively. 2 Although the muscle-liver crosstalk in chronic hepatitis C (CHC) is not wholly clarified, we observed a dynamic reduction in non-invasive markers of hepatic fibrosis and increased muscle mass in patients who have achieved HCV eradication.…”
mentioning
confidence: 80%
“…
We thank Drs Tian and Ngu for their insightful comments on our study, and we would like to make some further observations. 1,2 We agree that skeletal muscle loss is significantly related to adverse clinical outcomes among patients with chronic liver disease in terms of morbidity and mortality. 3 More recently, a meta-analysis showed that the overall prevalence of sarcopenia among patients with cirrhosis is approximately 40.0%.
…”
mentioning
confidence: 85%